Petrogenesis and tectonic setting of the Cretaceous volcanic-intrusive complex in the Zijinshan ore district, Southeast China: Implications for different stages of mineralization. (1st May 2020) - Chi, Zhe; Ni, Pei; Pan, Jun-Yi; Li, Su-Ning; Wang, Guo-Guang; Yang, Yu-Long; Xue, Kai; Liao, Jian-Feng
Graphical abstract: Highlights: Superimposition of magmatic events led to various styles of mineralization in the Zijinshan ore district. The involvement of mantle materials was critical for the formation of the early Cu-Au deposits. More crustal materials and highly evolved magmas were the key in the formation of the late stage of Ag-Pb-Zn mineralization. The extension triggered melting of the metasomatized mantle to form ore-forming magmas. Abstract: Volcanic–subvolcanic rocks and associated Cu-Au-Ag-Pb-Zn mineralization within the Zijinshan ore district, located in the southwestern part of Fujian Province, represent a large metallogenic district within the southeastern coastal volcanic belt of China. This study presents new whole-rock geochemical, Sr–Nd–Hf isotopic, and zircon trace element data for igneous rocks within the Zijinshan area. Combining these new data with previously published geochronological results allows to constrain the magmatic and hydrothermal history and to understand the ore-related geological setting. Our results provide evidence of multi-stage metallogenic events within the Zijinshan district that can be roughly divided into early stage Cu-dominant (ca. 105–102 Ma) and late-stage Pb-Zn-enriched Ag-polymetallic (ca. 95–92 Ma) mineralization. Igneous rocks associated with the early stage of mineralization are enriched in the large ion lithophile elements (LILEs), depleted in the high field strength elements (HFSEs) with negative Nb, Ta and Ti anomalies, and have relatively high Mg # (35.9–63.5), low initial 87 Sr/ 86 Sr (0.7065–0.7088), relatively depleted εNd(t) and εHf(t) values (-3.6 to −2.3 and −5.04 to 0.85, respectively), and younger two-stage Hf model ages (1.4–1.1 Ga), suggesting that the components from metasomatized mantle were incorporated. The zircons in these early stage rocks are with elevated Ce 4+ /Ce 3+ values (358–1029) indicating the high oxygen fugacity. In comparison, the igneous rocks associated with the late stage of mineralization have high initial 87 Sr/ 86 Sr values (0.7071–0.7103), enriched εNd(t) and εHf(t) values (−6.6 to −5.5 and −8.92 to −4.15, respectively), and older two-stage Hf model ages (1.7–1.4 Ga), that are indicative of formation from magmas that incorporated ancient crustal material. The late-stage igneous rocks contain zircons with low Ce 4+ /Ce 3+ values (20–387) that are indicative of low oxygen fugacity conditions. Besides, the late stage ore-related igneous rocks are of high silica contents with highly evolved chemical signatures, indicative of intensive fractionation processes. The diverse metal endowments may be attributed to different sources, oxygen fugacity and magmatic evolution levels of the ore-related magmas. The Cretaceous magmas in Zijinshan were likely generated under an extensional setting. The lithospheric extension triggered partial melting of the fertile metasomatized subcontinental mantle, incorporating a large amount of mantle-derived components and generated the early Cu-Au-Mo mineralization. Later, a local and temporary shift to the more compressional environment would weaken the contribution of mantle. More ancient crustal materials were incorporated in the late stage and the magmas underwent intensive fractional crystallization, leading to the generation of Ag-polymetallic mineralization in the Zijinshan ore district.